Problemy pomiaru wiedzy językowej - Pawlak, Mirosław (Neofilolog, 2010)
A key issue in research projects exploring the effectiveness of foreign language learning and teaching is precise measurement of learners’ knowledge of the targeted structure before and after the pedagogic intervention with an eye to determining the value of specific instructional options. Such measurement, however, poses a considerable challenge because traditional tests focusing on grammar or lexis only provide information about explicit, declarative knowledge, which is conscious and can primarily be applied in situations in which learners have sufficient time to plan their responses. For this reason, it is also necessary to measure implicit, procedural knowledge which is subconscious and automatic, thus enabling successful participation in spontaneous communication where limited attentional resources have to be employed in understanding and conveying messages in real time. The aim of this paper is to characterize the two types of linguistic knowledge, present the tools that can be employed in their measurement, and demonstrate how instruments of this kind can be successfully utilized in empirical investigations aiming to verify the effectiveness of techniques and procedures in teaching grammar.